DUKUNGAN ARAB SAUDI TERHADAP REZIM PEMERINTAHAN HAMAD BIN ISA AL-KHALIFA PADA TAHUN 2011-2014 - Febrian Andri; Pazli " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
This research analyzes the reasons of saudi arabia gave support to the regime of Hamad bin Isa Al-Khalifa in 2011-2014. Saudi Arabia provides economic assistance through the GCC, security forces joint in Peninsula Shield Force, denounced the involvement of other countries in the internal affairs of Bahrain and to support the implementation of the national dialogue and independent fact-finding body as a solution to solving problems political crisis in Bahrain. This article applying qualitative research methods libarary research. The namely data source of books, journals, publications, articles, news and internet. The author uses theories have foreign policy by applying a theoretical model of policy making internal-external setting suggested by Richard Snyder, Burton Sapin and HW Burck and use the level of the nation-state analysis as an object of his research. Saudi Arabia supports the regime Hamad bin Isa Al-Khalifa because of political ideology and security threats. With the fact that the emergence of movements of pro-revolution, increasing demonstration in the eastern part of Saudi Arabia, as well as the actions and reactions of other countries that provide opportunities onset Shiite revolution in Bahrain. and increased fluctuations in the conflict in Bahrain would threaten the national security of Saudi Arabia as the security of citizens (tourists saudi), economic security, the security of the assets of diplomatic and security in the region.Keywords: Support, Hamad Bin Isa Al-Khalifa, Foreign policy, ideological politics, security threats